Cervical Schwannoma: A Rare Cause of Tracheal Stenosis Misdiagnosed as Asthma - Akira Naomi; Hideyuki Hujiwara; Tatsuhiko Koizumi; Yukari Sakurai; Yasuo Kohashi; Yukiko Yoneda; Yuka Kitamura; Yoshinobu Hattori; Yuji Saitou (Achievements and Challenges of Medicine and Medical Science Vol. 11, 2025)
Cases of upper tracheal stenosis due to cervical schwannoma are fairly rare, therefore, no treatment has been determined. Additionally, No surgical cases of upper tracheal stenosis caused by cervical schwannoma have been reported in the literature. This is a report of a case of cervical schwannoma with severe upper tracheal stenosis. In this case, a 48-year-old woman was treated with asthma for 4 years at another hospital, however, the patient was admitted to our hospital because of breathing difficulty. CT showed a tracheal stenosis lesion just below the vocal cords, and a biopsy revealed schwannoma. The tumour consisted of spindle-shaped cells, accompanied by collagen fibres, and no mitotic figures or atypia was observed; immunostaining revealed CD34 (-), S100 (+) and \(β\)-catenin (-), leading to the diagnosis of low-grade schwannoma. Regarding the treatment, conservative therapy is desired rather than tumor resection of the tumor by surgery, but the size of the tumor on the image and the patient’s condition have not been changed for 7 years. Once a year, conservative treatment is considered an option if the extratracheal tumor has not regrown.